The impact of public education on the construction of national identity: The legacy of Gabriel García Moreno - Tapia Chasi, Sara Alexandra; Quishpe Caranqui, Ricardo Gustavo; Fernández Ponce, Geovanna del Pilar; Juca Salazar, Silvana Mariela (RECIMUNDO, 2023)
Politics in relation to education, like the other manifestations of the superstructure of society, is a manifestation of the power of social groups in relation to the economic policies and relations of production in force in a given State, it arises in society at the time and place when the groups that hold political power need to express and preserve their dominion over economic interests. in contrast to those members of society who do not have power. Thus, in the Republic of Ecuador, progress in knowledge and technology was gradually transformed into the; Although it was not a completely radical change, it did represent a turning point in education and science. The educational policies implemented during the García Moreno administration focused on improving the quality of education provided by schools, in order to promote the development of students from a religious perspective based on the Catholic Church. These policies were adapted to the educational needs of the country and facilitated the development of a national identity in the cultural, scientific, technological, artistic and social aspects. The capacities of schools should be oriented to form values was of great importance, these educational policies promoted the development of education in Ecuador, especially benefiting women and indigenous people, who were always discriminated against. From this perspective, it can be noted that García Moreno ensured an education that satisfied human needs by providing essential scientific knowledge for society. He directed the formation of Ecuadorian citizens towards the socialization of norms, values and patterns associated with the Catholic Church, complemented by a European influence through the hiring of religious personnel to implement these educational policies; During his government, there was a clearly defined and specific educational policy.